2008
DOI: 10.1038/ejhg.2008.135
|View full text |Cite
|
Sign up to set email alerts
|

Search for copy number alterations in the MEFV gene using multiplex ligation probe amplification, experience from three diagnostic centres

Abstract: Familial mediterranean fever (FMF) is a hereditary autoinflammatory autosomal recessive disease caused by mutations in the MEFV gene. Despite the identification of many disease associated MEFV mutations, often the clinical diagnosis cannot be genetically confirmed. The currently used diagnostic sequencing techniques only allow the detection of point mutations, small deletions or duplications. The question as to whether larger genetic alterations are also involved in the pathophysiology of FMF remains to be ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
2
12
0
2
Order By: Relevance
“…14,15 Moreover, a few studies have shown that mutations from other autoinflammatory disorders, as well as MEFV expression levels and copy-number variation, similarly may not be a major contributing factor for FMF symptoms in heterozygous patients. 16,17,18 Findings from these studies along with our results support the notion that some MEFV mutations may act as a dominantly inherited trait and cause mild FMF cases. Our statistical analysis indicated high probabilities for the presence of symptoms, common to homozygous FMF cases, in heterozygous patients.…”
Section: Discussionsupporting
confidence: 87%
“…14,15 Moreover, a few studies have shown that mutations from other autoinflammatory disorders, as well as MEFV expression levels and copy-number variation, similarly may not be a major contributing factor for FMF symptoms in heterozygous patients. 16,17,18 Findings from these studies along with our results support the notion that some MEFV mutations may act as a dominantly inherited trait and cause mild FMF cases. Our statistical analysis indicated high probabilities for the presence of symptoms, common to homozygous FMF cases, in heterozygous patients.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, it is our observation that a significant proportion of patients have an incompletely explained clinical diagnosis from a molecular genetics standpoint. 15 In such situations, we tend to accept the DNA findings as supportive of FMF and presume that the second mutation is not detected due to rarity or location outside the analyzed gene regions.…”
Section: Molecular Genetic Testingmentioning
confidence: 99%
“…15 Thus, it is possible in individuals in which only one mutation is identified that a second disease-causing mutation may reside in a noncoding intronic area or in a gene regulatory region affecting messenger RNA splicing or expression. Furthermore, the medical literature suggests that single and multiexon MEFV copy number changes (i.e., large deletions or duplications) do not contribute to the pathogenesis of FMF; for this reason, multiplex ligation-dependent probe amplification and other gene rearrangement techniques are not generally recommended for FMF testing.…”
Section: Molecular Genetic Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…The carrier frequency of MEFV mutations is quite high in the 4 classically affected populations, ranging from 37 to 39% in Armenians and Iraqi Jews to 20% in Turks, North African and Ashkenazi Jews and Arabs (Pras and Kastner, 1997;Shinar et al, 2000;Schouten et al, 2002, van Gijn et al, 2008.…”
Section: Introductionmentioning
confidence: 99%